2019
DOI: 10.1080/10942912.2019.1588902
|View full text |Cite
|
Sign up to set email alerts
|

Roasted tree peony ( Paeonia ostii ) seed oil: Benzoic acid levels and physicochemical characteristics

Abstract: Tree peony seeds oil (TPSO, Paeonia ostii) extracted at different roasting temperatures were studied for color, acid values, total phenols, fatty acid composition, antioxidant capacity, volatiles, and benzoic acid. Roasting led to increased antioxidant capacity and acid values. Headspace analysis of raw peony seed oil showed only six volatile compounds, while after roasting volatiles such as pyrazines, aldehydes and furans were observed and contributed to nutty aromas. Unsaturated fatty acids constituted more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The study has shown that the composition and content of volatile compounds in peanut oil changed significantly after roasting pretreatment, and the contents of O‐heterocyclic compounds and N‐heterocyclic compounds accounted for a relatively high proportion, of which 20 pyrazines were considered as key contributors to the typical nut and roasting aroma of peanut oil (Liu et al., 2011). Similar studies have been done in sesame oil, rapeseed oil, palm kernel oil, almond oil, pumpkin seed oil, and peony seed oil (Jin et al., 2018; Jin et al., 2019; Jing et al., 2020; Potočnik & Košir, 2017; Yan et al, 2012; Zhang et al., 2016). Microwave, as a new heating technology, is gradually applied to oil processing.…”
Section: Introductionsupporting
confidence: 59%
“…The study has shown that the composition and content of volatile compounds in peanut oil changed significantly after roasting pretreatment, and the contents of O‐heterocyclic compounds and N‐heterocyclic compounds accounted for a relatively high proportion, of which 20 pyrazines were considered as key contributors to the typical nut and roasting aroma of peanut oil (Liu et al., 2011). Similar studies have been done in sesame oil, rapeseed oil, palm kernel oil, almond oil, pumpkin seed oil, and peony seed oil (Jin et al., 2018; Jin et al., 2019; Jing et al., 2020; Potočnik & Košir, 2017; Yan et al, 2012; Zhang et al., 2016). Microwave, as a new heating technology, is gradually applied to oil processing.…”
Section: Introductionsupporting
confidence: 59%
“…The most dominant heterocyclic substances were 4,7-dimethylbenzofuran and 2,6-dimethylpyrazine, which were significantly increased under RF, MW and RT treatment at 140 °C ( p < 0.05). Previous research indicated that pyrazines contribute to the roasted aroma [ 15 ]. Some alcohols, phenol, and acids were also detected in the TPSO sample of different treatments.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed that RT treatment compromises several of the physicochemical properties of chia seeds [ 14 ]. Excessive RT heating of TPSO produces high contents of benzoic acid [ 15 ], which results in poor oil quality. Microwave heating, which was considered to be a new high-efficiency and promising technology has been widely used in many processes, including in the processing of rapeseed and camellia seed, to improve the texture and the release of nutrient components and enhance its antioxidant effects [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…67 Increasing the roasting temperature leads to an increase in the total phenolic content (TPC) of roasted TPSO. 74 When the roasting temperature is increased from 120 °C to 150 °C, the TPC in TPSO increases from 37.8 µg gallic acid equivalent to 49.6 µg mL −1 methanol extract. 74 Although phenolics are degraded at high temperatures, an appropriate increase in baking temperature can promote the Maillard reaction, resulting in the generation of the corresponding antioxidant products.…”
Section: Phenolicsmentioning
confidence: 99%
“…74 When the roasting temperature is increased from 120 °C to 150 °C, the TPC in TPSO increases from 37.8 µg gallic acid equivalent to 49.6 µg mL −1 methanol extract. 74 Although phenolics are degraded at high temperatures, an appropriate increase in baking temperature can promote the Maillard reaction, resulting in the generation of the corresponding antioxidant products. The TPC, total flavonoid content (TFC), and total flavanol content (TAC) of peony seeds from different species and their antioxidant activities differ.…”
Section: Phenolicsmentioning
confidence: 99%